ANALYZING CHALLENGES IN ESTIMATING TIME AND COST IN SOFTWARE PROJECTS - Muhammad Kashif Khan,; Syed Zaffar Iqbal,; Palwasha Khalid, (Spectrum of Engineering Sciences, 2025)
Accurately estimating time and cost in software projects remains a persistent challenge that significantly influences project success. Despite the availability of various estimation models and techniques, many projects still face delays and budget overruns due to factors such as ambiguous requirements, tool limitations, and organizational complexity. This study aims to explore and analyze the key challenges software practitioners encounter in the estimation process. Adopting a qualitative research design, data were collected through semi-structured interviews, focus groups, and document analysis involving experienced software professionals from diverse development environments. Thematic analysis, supported by coding techniques using NVivo, revealed five major themes: requirement ambiguity, limitations in estimation tools, human bias and experience, agile and iterative complexity, and organizational and external influences. These findings highlight that estimation difficulties are multidimensional and deeply rooted in both technical and socio-organizational factors. The study contributes to the understanding of how these challenges interact and offers insights for improving estimation practices through adaptive models and enhanced stakeholder engagement.